Analisis Kinerja Bank-Bank Jepang Versus Bank-Bank Asing Non Jepang di Indonesia - Andreas dan Suwinto Johan (Universitas Tarumanagara, 2020)
Analisa kinerja Bank-Bank Jepang versus Bank-Bank Asing Non Jepang di Indonesia was method how people realize when placed their money. This research was important to be studied to find out performance of Japanese Banking beside foreign banking in Indonesia in 5 years form period 2013-2019. This research studies based on liquidity ratios, leverage ratios, activity ratios, profitability ratios, and managerial implications. researcher using t-test, sign test, and wilocoxon test for supported this research. This research can be conclusion about cause of difference and raised financial performance between Japan Bank and foreign Bank because, there are factors that infulnce Japanese banks' capital adequacy which pay great attention to lending in Indonesia. than non-Japanese foreign banks in Indonesia.